Development of contact allergy diagnostics - Żmudzińska, Maria; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
First researches on diagnostics of allergic contact dermatitis known as immunological type IV reaction according to Gell and Coombs classification were performed at the end of XIX th century. Understanding of the mechanisms of allergic delayed hypersensitivity resulted in patch tests commonly used nowadays on allergological diagnostics. European standard series of contact allergens are being processed by European Environmental and Contact Dermatitis Research Group (EECDRG), British Contact Dermatitis Group (BCDG) and International Contact Dermatitis Group (ICDRG). Proper diagnostics of contact allergy to topical glucocorticosteroids is considered as a problem of both clinical and scientific importance. This paper presents development of contact allergy diagnostics where the most current problem of anti-inflammatory and antiallergic medications is being discussed.